Decision Support System to Determine the Success Rate of Teaching Teachers at Nur Fadhillah Elementary School Medan with SAW Method - Herdwiyani, Putri; Ginting, Subhan Hafiz Nanda; Purwawijaya , Ellanda (PT. Technology Laboratories Indonesia (TechnoLabs), 2024)
This research aims to develop and implement a Decision Support System (DSS) to determine the success rate of teachers in teaching at SD Nur Fadhillah Medan using the Simple Additive Weighting (SAW) method. The SAW method was chosen because of its ability to provide an objective assessment through a weighted summation process of each evaluated criterion. This research involves several assessment criteria such as pedagogical competence, communication skills, attendance, and feedback from students. The data obtained is processed using the SAW method to produce a final score that describes the success rate of each teacher. The results of this research are expected to help the school in making more effective and objective decisions related to teacher performance evaluation, so as to improve the quality of education in the school. Thus, the implementation of this DSS is expected to be a useful tool for school managers in identifying areas of improvement and giving proper appreciation to teachers.